A Randomized Controlled Trial of Attention Bias Modification Treatment in Youth With Treatment-Resistant Anxiety Disorders - Pettit, Jeremy W; Bechor, Michele; Rey, Yasmin; Vasey, Michael W; Abend, Rany; Pine, Daniel S; Bar-Haim, Yair; Jaccard, James; Silverman, Wendy K (Journal of the American Academy of Child and Adolescent Psychiatry, 2020)
Randomized clinical trials of augmentation strategies for youth with treatment-resistant anxiety disorders do not exist. This report presents findings from an efficacy trial of attention bias modification treatment (ABMT) as an augment for this population compared with attention control training (ACT). Sixty-four youths (34 boys; mean age 11.7 years) who continued to meet for anxiety diagnoses after completing cognitive-behavioral therapy were randomized to ABMT or ACT. ABMT and ACT consisted of dot-probe attention training trials presenting angry and neutral faces; probes appeared in the location of neutral faces on 100% of trials in ABMT and 50% of trials in ACT. Independent evaluators, youths, and parents completed ratings of youth anxiety severity, and youths completed measures of attention bias to threat and attention control at pretreatment, post-treatment, and 2-month follow-up. The 2 arms showed significant decreases in anxiety severity, with no differences between arms. Specifically, across informants, anxiety severity was significantly decreased at post-treatment and decreases were maintained at follow-up. Primary anxiety disorder diagnostic recovery combined across arms was 50% at post-treatment and 58% at follow-up. Attention control, but not attention bias to threat, was significantly improved at post-treatment in the 2 arms. This is the first study to show anxiety can be decreased in youth who did not respond to cognitive-behaviorial therapy, and that the anxiety-decreasing effect is found using these 2 attention training contingency schedules. These findings and increases in attention control in the 2 arms raise intriguing questions about mechanisms of decreasing anxiety in treatment-resistant youth with attention training that require further research. Attention Bias Modification Training for Child Anxiety CBT Nonresponders; https://clinicaltrials.gov/; NCT01819311.